Prevalence of Overweight and Obesity among Pre-adolescence school children at Al- Nasiriya city, Iraq - Rawaa Kamel Abd; Sameeha Naser Abd; Makki Hasan Kadhim; Sana Rouis; Mahdi Boutrif (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the sociodemographic factors and determine the prevalence of overweight and obesity among students in their early adolescent years. Method: The cross-sectional study was conducted at four governmental intermediate schools located in Al-Nasiriya city of Thi-Qar Governorate in Iraq from January 2 to February 15, 2021, and comprised students of either gender aged 12-14 years. Data was gathered using a self-designed questionnaire. Body mass index was calculated after measuring the subjects’ weight in kilograms on a properly calibrated digital scale and their height in centimetres on an appropriate tape meter scale. Data was analysed using SPSS 23. Results: Of the 218 subjects, 124(56.88%) were girls and 94(43.12%) were boys. Overall, 100(45.87%) subjects were aged 13 years. There were 71(32.56%) overweight and 30(13.76%) obese subjects. Age and gender were significantly associated with body mass index (p<0.05). Conclusion: Students in their early adolescent years were relatively more likely to be overweight and obese. Age and gender had a correlation with body mass index. Keywords: Overweight, Body mass, Paediatric, Obesity, Demography.